Calculating core‐level excitations and x‐ray absorption spectra of medium‐sized closed‐shell molecules with the algebraic‐diagrammatic construction scheme for the polarization propagator. Issue 26 (7th August 2014) - Wenzel, Jan; Wormit, Michael; Dreuw, Andreas
<x xml:space="preserve">Abstract</x> Core‐level excitations are generated by absorption of high‐energy radiation such as X‐rays. To describe these energetically high‐lying excited states theoretically, we have implemented a variant of the algebraic‐diagrammatic construction scheme of second‐order ADC(2) by applying the core‐valence separation (CVS) approximation to the ADC(2) working equations. Besides excitation energies, the CVS‐ADC(2) method also provides access to properties of core‐excited states, thereby allowing for the calculation of X‐ray absorption spectra. To demonstrate the potential of our implementation of CVS‐ADC(2), we have chosen medium‐sized molecules as examples that have either biological importance or find application in organic electronics. The calculated results of CVS‐ADC(2) are compared with standard TD‐DFT/B3LYP values and experimental data. In particular, the extended variant, CVS‐ADC(2)‐x, provides the most accurate results, and the agreement between the calculated values and experiment is remarkable. © 2014 Wiley Periodicals, Inc.